A general strategy for overcoming the trade-off between ultrasmall size and high loading of MOF-derived metal nanoparticles by millisecond pyrolysis. (15th June 2022) - Han, Ye-Chuang; Liu, Meng-Li; Sun, Li; Li, Xu-Cheng; Yao, Yonggang; Zhang, Chao; Ding, Song-Yuan; Liao, Hong-Gang; Zhang, Li; Fan, Feng Ru; Moskovits, Martin; Tian, Zhong-Qun
Abstract: Metal-organic frameworks (MOFs) have flourished as a library of promising precursors for synthesizing carbon-supported metal catalysts by pyrolysis, but it is extremely difficult to simultaneously achieve a high metal loading and an ultrasmall size, particularly for non-noble metal (Fe, Co, Ni, etc.) that are highly active and have a strong tendency to coarsen. Here, we report a general strategy for controllable synthesize thermodynamically metastable sub-3 nm non-noble metal nanoparticles (NPs) with ultrahigh metal loading up to 41.0 wt% (12.8 at%) by rapid pyrolysis of MOF (e.g., ~ 1000 °C in 0.3 s), at least four-fold higher than the reported strategy where ultrasmall NPs were obtained but with a significant sacrifice of metal loading (usually less than 10 wt%). Furthermore, we found that the formation of metal NPs during high-temperature pulse agrees with the LaMer model (sigmoidal coarsening kinetics), in which rapid pyrolysis triggers only the initial nucleation and avoids Ostwald ripening or further coalescence. We also demonstrate the generality of our strategy in synthesizing other MOF-derived ultrasmall NPs, including non-noble metal NPs (Ni), metallic compound (CoS2 ), and alloy (CoPd). As a demonstration, the obtained CoPd-based catalyst showed high activity and robust stability during prolonged catalytic reactions. Therefore, our strategy and mechanistic insights enable the rational design and controlled synthesis of advanced catalysts with a good balance between ultrasmall size and a high metal loading, from more than 100, 000 types of MOFs. Graphical Abstract: ga1 The long-standing trade-off between ultrasmall size and high loading of MOF-derived metal nanoparticles is overcome by millisecond pyrolysis strategy. This general strategy enable the rational design and controlled synthesis of advanced catalysts with a good balance between ultrasmall size and a high metal loading, from more than 100, 000 types of MOFs. Highlights: A general strategy for achieving both ultrasmall size and high loading in heterogeneous metallic catalysts is proposed. Sub-3 nm Co nanoparticles with a high Co loading up to 41 wt% was synthesized by millisecond pyrolysis of MOF. The nucleation and growth of MOF-derived metal nanoparticles in high-temperature pulse fit with the LaMer model. The as-prepared catalyst showed high activity and robust stability during prolonged electrocatalytic reactions.